2023
DOI: 10.1007/s00417-023-06072-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete blood count parameters as biomarkers of retinopathy of prematurity: a Portuguese multicenter study

Abstract: Purpose To evaluate complete blood count (CBC) parameters in the first week of life as predictive biomarkers for the development of retinopathy of prematurity (ROP). Methods Multicenter, prospective, observational study of a cohort of preterm infants born with gestational age (GA) < 32 weeks or birth weight < 1500 g in eight Portuguese neonatal intensive care units. All demographic, clinical, and laboratory data from the first week of life were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…Our study shows significant differences in the blood count of the first week of life between infants who subsequently develop ROP and those who do not. Higher erythroblast counts and RDW, as well as lower mean hemoglobin levels and MCHC, are significantly associated with the development of ROP, which is in line with the work we previously reported [43]. Of these parameters related with anemia, only mean hemoglobin levels lose statistical significance after adjustment for GA and number of days of red blood cell transfusion, risk factors associated with ROP after logistic regression analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows significant differences in the blood count of the first week of life between infants who subsequently develop ROP and those who do not. Higher erythroblast counts and RDW, as well as lower mean hemoglobin levels and MCHC, are significantly associated with the development of ROP, which is in line with the work we previously reported [43]. Of these parameters related with anemia, only mean hemoglobin levels lose statistical significance after adjustment for GA and number of days of red blood cell transfusion, risk factors associated with ROP after logistic regression analysis.…”
Section: Discussionsupporting
confidence: 90%
“…However, reports on RBC parameters, such as RDW and ROP, are limited. 21 In our study, RDW, MCH, and MCV were not independent risk factors for ROP after adjusting for multiple confounders. These differences may be due to variable sample sizes, gestational ages, birth weights, follow-up times, case de nitions, and adjustments for confounding factors.…”
Section: Discussioncontrasting
confidence: 42%
“…gestational age, birth weight, SGA, oxygen supplementation on DOL 28, mechanical ventilation on DOL 28, and RBC transfusion before DOL 28. 21…”
Section: Outcomes and Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search process PRISMA flow diagram is depicted in Figure S1. Of 2645 studies with potential relevance, 21 were included [6,7,9,10,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. These studies reported on 3625 infants.…”
Section: Characteristics Of the Studies And Risk Of Bias Assessmentmentioning
confidence: 99%